ANALISIS SEGMENTASI, TARGETING, DAN POSITIONING PADA PT SIANTAR TOP TANJUNG MORAWA - Yunita, Irma; Fikrianda, Rifki; Syafrizal, Muhammad; Siregar, Jamaluddin; Suhairi, Suhairi (Jurnal Manajemen Akuntansi (JUMSI), 2021)
This study aims to determine how the marketing strategy of STP at PT Siantar Top Tanjung Morawa. This research is a descriptive research. This research uses case study research techniques. Data collection techniques in this study use interviews and documentation. Interviews were used using tools, namely questionnaires and documentation methods to obtain secondary data. The population used in this study were all consumers of the products of PT Siantar Top Tbk Tanjung Morawa. Respondents in this study were 100 respondents. The sampling technique is simple random sampling. The results of this study are based on the results of the analysis carried out by segmentation, targeting, and positioning simultaneously have a significant effect on purchasing decisions. Based on the test results, it was found that the segmentation variable had a positive influence on the product purchase decision of PT Siantar Top Tbk. Based on the test results, it was found that the targeting variable had a positive influence on the product purchase decision of PT Siantar Top Tbk. Based on the test results, it was found that the positioning variable had a negative influence on the product purchase decision of PT Siantar Top Tbk.